"Less pain with more gain"—Managing wound‐related pain with cannabis‐based medicines. Issue 2 (22nd January 2021) - Maida, Vincent; Biasi, Stefano A
Abstract: Wound‐related pain poses a serious challenge for patients and physicians. It is a complex pathophysiologic construct that may be stratified, from the patient's perspective, into baseline pain and breakthrough pain. The current paradigm for treating wound related pain involves the overuse of opioids and other co‐analgesics with little regard for breakthrough pain. These standard medications have a propensity for deleterious side effects while some of them inhibit wound healing, effectively perpetuating the wound and the related pain. In particular, the overuse of opioids is a contributor to the global opioid crisis. It is evident that a new paradigm needs to be considered. Cannabis‐based medicines are a prominent prospect under investigation for their potential to reduce dosages of status quo analgesics while effectively reducing pain. The authors propose a new paradigm that emphasizes the use of Cannabis‐Based Medicines, delivered through multiple routes, while recommending the need for more foundational scientific investigation into mechanisms, and clinical controlled trials to determine optimal combinations, dosages, and protocols.